2007
DOI: 10.1177/000348940711600310
|View full text |Cite
|
Sign up to set email alerts
|

Vortical Flow Field during Phonation in an Excised Canine Larynx Model

Abstract: Objectives-To more fully understand the mechanisms of vocal fold vibration and sound production, we studied the velocity flow fields above the folds. Such velocity fields during phonation have not been reported in the literature. Methods-Using the particle image velocimetry method for 3 excised canine larynges, we obtained the velocity fields in the mid-membranous coronal plane during different phases of phonation. The velocity field was determined synchronously with the vocal fold motion recorded by high-spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 17 publications
(16 reference statements)
2
67
0
Order By: Relevance
“…Previous studies showed that the physical model exhibited qualitatively similar vibratory pattern (Zhang et al, 2006b(Zhang et al, , 2009) and supraglottal flow field pattern (Neubauer et al, 2007;Drechsel and Thomson, 2008) to that observed in excised-larynx (Khosla et al, 2007) and in-vivo canine models (Dollinger et al, 2005). In general, the vocal fold models exhibited vibratory patterns (e.g., onset frequency and pressure, pressure-flow relationship, vibration amplitude, and flow modulation, etc.)…”
Section: Methodsmentioning
confidence: 59%
“…Previous studies showed that the physical model exhibited qualitatively similar vibratory pattern (Zhang et al, 2006b(Zhang et al, , 2009) and supraglottal flow field pattern (Neubauer et al, 2007;Drechsel and Thomson, 2008) to that observed in excised-larynx (Khosla et al, 2007) and in-vivo canine models (Dollinger et al, 2005). In general, the vocal fold models exhibited vibratory patterns (e.g., onset frequency and pressure, pressure-flow relationship, vibration amplitude, and flow modulation, etc.)…”
Section: Methodsmentioning
confidence: 59%
“…Another aspect of the fluidstructure interaction that may be oversimplified in this study is the use of a one-dimensional flow model. More realistic flow models need to be used so that the effects of realistic flow features (e.g., flow curvature effects, asymmetric flow pressure, and vortex shedding; Erath and Plesniak, 2006;Neubauer et al, 2007;Khosla et al, 2007) can be considered. For example, it is possible that non-FM modes may participate in synchronization if a non-uniform flow pressure distribution along the AP direction is allowed, which may happen in realistic phonation.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Intraglottal vorticity-velocity interaction, glottal jet structure, and its transition to turbulence are all demonstrated to be highly three-dimensional (3D) (McGowan, 1988;Neubauer et al, 2007;Triep et al, 2005;Triep and Br€ ucker, 2010;Zheng et al, 2011b). The 3D effects are clearly observed in the supraglottal region in both the experimental Triep and Br€ ucker, 2010;Khosla et al, 2007;Khosla et al, 2008) and numerical studies (Zheng et al, 2010b;Mattheus and Br€ ucker, 2011). The asymmetric flow deflection in the 3D models is also observed to be different from the 2D models.…”
Section: Introductionmentioning
confidence: 97%